Meat-egg-dairy consumption and depressive symptoms among Chinese older adults: exploring rural/urban and gender disparities - Si, Boyu; Zhang, Keqing (Frontiers in Psychiatry, 2024)
IntroductionThis study examines the association between Meat, Egg, and Dairy (MED) product consumption and depressive symptoms among older adults in China, focusing on rural/urban and gender differences.MethodsThis study employed data from the latest wave (year 2018) of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), and Ordinary Least Squares (OLS) models were applied to examine the association between MED consumption and depression levels.FindingsThe findings revealed a consistent negative relationship between MED consumption and depression, with higher MED intake associated with lower depression levels. Urban residents and males exhibited higher MED consumption, which correlated with less depressive symptoms. However, the impact of MED consumption on depression varied by subgroups; urban older adults benefited more from MED consumption than their rural counterparts, and the relationship between MED intake and depression was more pronounced in males than in females. The study highlighted the influence of socio-demographic factors, such as literacy, income, and self-rated health, on depression levels.DiscussionThe results suggested that MED consumption may offer protective effects on mental health in older adults, although the association may not be causal. The study underscored the need for further research to explore the complex interplay between diet and mental health in older adults, particularly in diverse cultural contexts.